2011
DOI: 10.1093/toxsci/kfr100
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Induces Anemia through Interdependent Progress of Hemolysis, Body Iron Accumulation, and Insufficient Erythropoietin Production in Rats

Abstract: Cadmium is a toxic heavy metal and distributed widely in the environment. In addition to damaging the liver, kidneys, and bone, cadmium causes anemia through hemolysis, iron deficiency, and insufficient erythropoietin (EPO) production (renal anemia) along with changes in iron metabolism. Here, we investigated the role of iron in the interdependent progress of three types of anemia in cadmium-injected rats fed iron-sufficient or iron-deficient diets for 1 or 3 months. Cadmium injections for 1 month induced rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 39 publications
5
62
0
1
Order By: Relevance
“…The Cd level in our study was lower than those which may be the reason of not significant difference. Three main factors are involved in the development of Cd-induced anemia: hemolytic, iron deficiency, and renal damage (Horiguchi et al, 2007;Horiguchi et al, 2011). It has been shown that exposure to Cd could impair the production of EPO in patients with Itai-Itai disease (Horiguchi et al, 1994) and results in the marked suppression of EPO mRNA expression in the kidneys (Horiguchi et al, 1996).…”
Section: Page 8 Of 20mentioning
confidence: 99%
See 1 more Smart Citation
“…The Cd level in our study was lower than those which may be the reason of not significant difference. Three main factors are involved in the development of Cd-induced anemia: hemolytic, iron deficiency, and renal damage (Horiguchi et al, 2007;Horiguchi et al, 2011). It has been shown that exposure to Cd could impair the production of EPO in patients with Itai-Itai disease (Horiguchi et al, 1994) and results in the marked suppression of EPO mRNA expression in the kidneys (Horiguchi et al, 1996).…”
Section: Page 8 Of 20mentioning
confidence: 99%
“…It has been indicated that Cd can induce anemia due to iron deficiency through competing with iron absorption (Hamilton and Valberg, 1974). Accumulation of Cd in organs would induce excess iron accumulation, which results in EPO suppression (Horiguchi et al, 2011). In addition, Pb is taken up by the iron absorption machinery, and secondarily blocks iron through competitive inhibition.…”
Section: Page 8 Of 20mentioning
confidence: 99%
“…Slides were stained with hematoxylin and eosin (H&E). Afterward, pathological sections were observed using an optical microscope and photographs were taken [13].…”
Section: Histopathologic Examinationmentioning
confidence: 99%
“…In another study by our group, we demonstrated that Cd could likely compete with ferrous iron to interact with the 5′-UTR iron response element of FPN's mRNA, affecting the translation of FPN (Sun et al, 2015). Additionally, it has been suggested that Cd may regulate hepcidin-mediated iron homeostasis by inducing the secretion of IL-6 (Horiguchi et al, 2011).…”
Section: Cadmium (Cd)mentioning
confidence: 89%